Drama for students. presenting analysis, context and criticism on commonly studied dramas - Greve, Jennifer; Milne, Ira Mark (Gale virtual reference library, 2007)
Features analysis of the plays most frequently studied in literature classes. Entries include: introduction providing overview of play; brief biography of playwright; plot summary; discussion of play's principal themes; understandable essays on play's construction; and excerpted critical commentary.